Health Benefits of Electrolyzed Hydrogen Water: Antioxidant and Anti-Inflammatory Effects in Living Organisms - Di Hu; Shigeru Kabayama; Yasuyoshi Watanabe; Yilong Cui (MDPI AG, 2024)
Molecular hydrogen, the smallest and lightest molecule, serves as an intense reducing agent. Its distinct characteristics, including minimal size and neutral charge, enhance bioavailability and facilitate significant biological effects. Previously considered physiologically inert, hydrogen has gained recognition as a powerful therapeutic agent, known for its antioxidative and anti-inflammatory properties. Electrolyzed hydrogen water (EHW), enriched with molecular hydrogen, demonstrates remarkable antioxidative capabilities, indicating potential benefits for various diseases. Inflammation-induced reactive oxygen species (ROS) amplify inflammation, leading to secondary oxidative stress and creating a crosstalk between ROS and inflammatory responses. This crosstalk contributes to the pathogenesis and progression of chronic diseases. EHW interrupts this crosstalk, reducing inflammatory cytokines and oxidative stress across various disease models, suggesting therapeutic potential. EHW is also known for its anti-inflammatory effects, extending to pain management, as evidenced in models like sciatic nerve ligation and inflammatory pain. In an inflammatory bowel disease (IBD) model, EHW effectively alleviates abdominal pain, mitigating 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced inflammation and oxidative stress, offering insights for clinical applications. Additionally, hydrogen selectively targets harmful radicals, and EHW intake helps balance stress-induced hormonal dysregulation, potentially easing disorders associated with chronic stress.